In Vitro Antimicrobial Activity Screening of Ethanol Extract of Lavandula stoechas and Investigation of Its Biochemical Composition - Canlı, Kerem; Yetgin, Ali; Benek, Atakan; Bozyel, Mustafa Eray; Murat Altuner, Ergin (Wiley, 2019)
The aim of this study was to test antimicrobial activity of ethanol extract of Lavandula stoechas against 22 bacteria and 1 yeast. Also, biochemical composition of the extract was investigated. A wide range of Gram-positive, Gram-negative microorganisms, and multidrug resistant bacteria were selected to test the antimicrobial activity. As a result, the extract is observed to contain fenchone (bicyclo[2.2.1]heptan-2-one, 1,3,3-trimethyl-, (1R)-) and camphor (+)-2-bornanone) as major components and showed antimicrobial activity against all studied microorganisms except Escherichia coli ATCC 25922 and Klebsiella pneumoniae. The results of the study present that L. stoechas is active against MDR strains too.
Keywords: Myrtenyl acetate; Lavandula stoechas; Unclassified drug; Antibiotic agent; Therapeutics. Pharmacology; RM1-950; Research Article; 3. Good health